Russian-Japanese relations during the early history of the Chinese Eastern Railway - Datsyshen V.G. (Японские исследования)
The article is devoted to the problems of Russian-Japanese relations on the Chinese Eastern Railway at the initial stage of its history. Workers from Japan were not invited to build the road, but the Japanese were already among the first settlers in the city of Harbin, founded in 1898 by the Chinese Eastern Railway Society. After a short break caused by the Russo-Japanese War, bilateral relations were quickly restored. In 1906, as the Russian troops withdrew from Manchuria, the Japanese began to return to the Chinese Eastern Railway. Since 1907, Japanese officials, entrepreneurs, cultural and sports figures from Japan began to take an active part in the socio-political, economic, and cultural life of the city of Harbin. It was here that the first “Russian-Japanese Society” was created. The Japanese in Harbin were mainly engaged in such areas as trade, medicine, entertainment, and domestic service. An important component of bilateral interaction was cooperation in the railway sector. Due to tradition and the inaccessibility of sources, the history of the Japanese population of Harbin is poorly studied in Russian historiography. The aim of this work is to reconstruct the historical picture and identify the problems of the Japanese presence in Harbin and Russian-Japanese interaction on the Chinese Eastern Railway in the period between the Russo-Japanese and the First World Wars. The study is based on materials from the Harbin periodical press, with the involvement of materials found in the archives collected by the researcher of the Chinese Eastern Railway E. K. Nilus. The information and analytical materials published in the newspapers Harbinskii Vestnik (“Harbin Bulletin”), Harbin, Novaya Zhizn’ (“New Life”), and Man'chzhurskii Kur'er (“Manchurian Courier”), especially advertising, allow one to get an idea of the composition of the Japanese community, the occupations of the Japanese and some problems of Russian-Japanese relations in 1906–1914. The study of development of the Chinese Eastern Railway by the Japanese, their coexistence and cooperation with Russians in Harbin will expand knowledge of the history of the Chinese Eastern Railway and achieve a more complete and objective picture of the history of Russian-Japanese relations in the 20th century.